Hot rolled steel plate
By optimizing the area ratio of martensite and tempered martensite in hot-rolled steel plates and controlling the finish rolling and cooling conditions, the problem of insufficient bending of existing hot-rolled steel plates is solved, and high strength and excellent bending are achieved .
Patent Information
- Application Number
- CN202280006571.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-01-15
- Filing Date
- 2022-01-07
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-01-07
AI Technical Summary
The existing high-strength hot-rolled steel plates have shortcomings in bending properties, which are difficult to meet the needs of automobile collision safety and environmental load reduction.
By setting the total area ratios of martensite and tempered martensite at 1/4 of the plate thickness of the steel plate to be more than 90%, and at a position 200 μm away from the surface to be more than 70% and less than 90%, and finely controlled rolling Conditions and cooling conditions to optimize metal structure.
It realizes the high strength and excellent bending of hot-rolled steel plates, meeting the needs of automobile collision safety and environmental load reduction.
Smart Images

Figure BDA0004138125400000191 
Figure BDA0004138125400000201 
Figure BDA0004138125400000211
Abstract
Description
Technical Field
[0001] The present invention relates to hot rolled steel sheets.
[0002] This application claims priority based on Japanese Patent Application No. 2021-005008 filed in Japan on January 15, 2021, and the contents are incorporated herein by reference. Background Art
[0003] In recent years, in order to ensure the collision safety of automobiles and reduce environmental loads, the high strength of steel plates is being developed. In order to increase the strength of steel plates, it is effective to make the metal structure into a single phase of martensite. Steel plates with a single phase of martensite metal structure have insufficient ductility compared to composite structure steel plates such as DP (Dual Phase) steel plates and TRIP (Transformation Induced Plasticity) steel plates, so in most cases they are mainly processed into the desired shape by bending. Therefore, steel plates as a single phase of martensite are required to have excellent bendability.
[0004] Patent document 1 discloses a high-strength hot-rolled steel plate with excellent low-temperature toughness, characterized in that it has the following structure: a martensite phase or a tempered martensite phase as the main phase, the volume fraction of the main phase relative to the entire structure is greater than 90%, the average grain size of the original austenite grains in the cross section parallel to the rolling direction is less than 20 μm, and in the cross section perpendicular to the rolling direction is less than 15 μm, and the aspect ratio of the original austenite grains in the cross section parallel to the rolling direction is less than 18.
[0005] Patent document 2 discloses a high-strength hot-rolled steel plate, characterized in that the steel structure has a main phase comprising at least one of a martensite phase and a tempered martensite phase and having an area ratio of more than 95% relative to the entire steel structure, and the laths of the martensite phase and / or the tempered martensite phase contain cementite with an average particle size of less than 0.5 μm, and the content of cementite is 0.01 to 0.08% by mass.
[0006] However, the inventors of the present invention have found that the steel sheets described in Patent Documents 1 and 2 cannot obtain sufficient bendability.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2016-211073
[0010] Patent Document 2: Japanese Patent Application Publication No. 2018-188675 Summary of the invention
[0011] Problems to be solved by the invention
[0012] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide a hot-rolled steel sheet having high strength and excellent bendability.
[0013] Means for solving problems
[0014] The inventors of the present invention conducted original research and, as a result, obtained the following knowledge, thereby arriving at the present invention.
[0015] It was recognized that a hot-rolled steel sheet with high strength and excellent bendability can be obtained by setting the total area ratio of martensite and tempered martensite to 90% or more in the metal structure at a position 1 / 4 of the plate thickness from the surface, and setting the total area ratio of martensite and tempered martensite to 70% or more and less than 90% in the metal structure at a position 200 μm from the surface.
[0016] Furthermore, the inventors of the present invention have found that, in order to obtain the above-mentioned hot-rolled steel sheet, it is effective to particularly control the finish rolling conditions and the cooling conditions after the finish rolling.
[0017] The gist of the present invention obtained based on the above findings is as follows.
[0018] (1) The chemical composition of the hot-rolled steel sheet according to one embodiment of the present invention contains, in terms of mass %, the following:
[0019] C: 0.050~0.150%,
[0020] Si: 0.01-1.00%,
[0021] Mn: 1.00~2.50%,
[0022] P: 0.100% or less,
[0023] S: 0.020% or less,
[0024] N: 0.0050% or less,
[0025] Al: 0.001~0.300%,
[0026] Ti: 0.001~0.100%,
[0027] B: 0.0005~0.0050%,
[0028] Nb: 0~0.100%
[0029] Cr: 0~1.00%,
[0030] V: 0~0.30%,
[0031] Cu: 0-0.30%,
[0032] Ni: 0-0.30%, and
[0033] Ca: 0~0.0050%,
[0034] The rest contains Fe and impurities.
[0035] Vc represented by the following formulas (1) to (3) is 10 to 40,
[0036] Metallic structure in area %:
[0037] At the 1 / 4 thickness position, at least one of martensite and tempered martensite: a total of 90% or more, and at least one of ferrite, bainite and pearlite: a total of 10% or less;
[0038] At a position 200 μm from the surface, at least one of martensite and tempered martensite accounts for 70% or more and less than 90% in total, and at least one of ferrite, bainite and pearlite accounts for more than 10% and less than 30% in total.
[0039] When the effective B content is ≥ 0.0005 mass %,
[0040] Vc=10 2.94-0.75×(2.7×C+0.4×Si+Mn+0.45×Ni+0.8×Cr)
[0041] When the effective B content is less than 0.0005 mass%,
[0042] Vc=10 3.69-0.75×(2.7×C+0.4×Si+Mn+0.45×Ni+0.8×Cr) (1)
[0043] Effective B content = 10.81 × (B / 10.81-solid solution N content / 14.01) (2)
[0044] Solid solution N content = 14.01 × (N / 14.01-Ti / 47.88) (3)
[0045] The symbol of each element in the above formula (1) represents the content of the element in mass %, and 0 is substituted when the element is not contained.
[0046] B in the above formula (2) is the B content expressed in mass %. When the effective B amount is a negative value, the effective B amount is set to 0.
[0047] In the above formula (3), N and Ti are contents expressed in mass %. When the amount of dissolved N is a negative value, the amount of dissolved N is set to 0.
[0048] (2) According to the hot-rolled steel sheet described in (1) above, the chemical composition may contain one or more of the following elements in terms of mass %:
[0049] Nb: 0.005~0.100%
[0050] Cr: 0.005~1.00%,
[0051] V: 0.005~0.30%,
[0052] Cu: 0.005-0.30%,
[0053] Ni: 0.005-0.30%, and
[0054] Ca: 0.0010~0.0050%.
[0055] (3) According to the hot-rolled steel sheet described in (1) or (2), in the metal structure, the average aspect ratio of prior austenite grains at the 1 / 4 position of the plate thickness may be 1.0 to 3.0.
[0056] (4) In the hot-rolled steel sheet according to any one of (1) to (3), the metal structure may have an average grain size of prior austenite grains of 5 to 40 μm at a position of 1 / 4 of the plate thickness.
[0057] Effects of the Invention
[0058] According to the above aspects of the present invention, a hot-rolled steel sheet having high strength and excellent bendability can be provided. DETAILED DESCRIPTION
[0059] Hereinafter, the hot-rolled steel sheet of the present embodiment will be described in detail. However, the present invention is not limited to the configuration disclosed in the present embodiment, and various modifications can be made without departing from the gist of the present invention.
[0060] For the numerical ranges described below with "to" between them, the lower limit and the upper limit are included in the range. For the numerical values expressed as "lower than" or "exceeding", the values are not included in the numerical range. All "%" about chemical composition means "mass %".
[0061] The chemical composition of the hot-rolled steel sheet of the present embodiment contains, by mass%, C: 0.050-0.150%, Si: 0.01-1.00%, Mn: 1.00-2.50%, P: 0.100% or less, S: 0.020% or less, N: 0.0050% or less, Al: 0.001-0.300%, Ti: 0.001-0.100%, B: 0.0005-0.0050%, and the remainder: Fe and impurities. Each element is described below.
[0062] C: 0.050~0.150%
[0063] C increases the strength of the hot-rolled steel sheet. If the C content is less than 0.050%, the desired strength cannot be obtained. Therefore, the C content is set to 0.050% or more. The C content is preferably 0.070% or more.
[0064] On the other hand, if the C content exceeds 0.150%, the weldability and toughness of the hot-rolled steel sheet decrease. Therefore, the C content is set to 0.150% or less. The C content is preferably 0.130% or less or 0.110% or less.
[0065] Si: 0.01~1.00%
[0066] Si improves the strength of hot rolled steel sheets by solid solution strengthening and hardenability improvement. In addition, Si also has a deoxidizing effect. When the Si content is less than 0.01%, the effects brought by the above effects cannot be obtained. Therefore, the Si content is set to 0.01% or more.
[0067] On the other hand, if the Si content exceeds 1.00%, ferrite transformation is promoted and the desired metal structure cannot be obtained. Therefore, the Si content is set to 1.00% or less. The Si content is preferably 0.40% or less or 0.30% or less.
[0068] Mn: 1.00~2.50%
[0069] Mn improves the strength of hot rolled steel sheets by solid solution strengthening and hardenability improvement. When the Mn content is less than 1.00%, the above effects cannot be obtained. Therefore, the Mn content is set to 1.00% or more. The Mn content is preferably 1.50% or more or 1.80% or more.
[0070] On the other hand, even if the Mn content is set to more than 2.50%, the above effect is saturated. Therefore, the Mn content is set to 2.50% or less. The Mn content is preferably 2.30% or less or 2.20% or less.
[0071] P: 0.100% or less
[0072] P reduces the bendability of the hot-rolled steel sheet. Therefore, the P content is set to 0.100% or less. The P content is preferably 0.020% or less.
[0073] The lower the P content, the better, and thus 0% is preferred. However, since excessive P reduces the P removal cost, the P content may be set to 0.001% or more.
[0074] S: 0.020% or less
[0075] S reduces the bendability of the hot-rolled steel sheet. Therefore, the S content is set to 0.020% or less. The S content is preferably 0.010% or less.
[0076] The lower the S content, the better, and thus 0% is preferred. However, since excessive S increases the cost of desulfurization, the S content may be set to 0.001% or more.
[0077] N: 0.0050% or less
[0078] N reduces the workability of the hot-rolled steel sheet. Therefore, the N content is set to 0.0050% or less. The N content is preferably 0.0040% or less.
[0079] The lower the N content, the better, and thus 0% is preferred. However, since excessive N content increases the cost of N removal, the N content may be set to 0.0010% or more.
[0080] Al: 0.001~0.300%
[0081] Al has the effect of cleaning the steel by deoxidation (suppressing defects such as bubbles in the steel). This effect cannot be obtained when the Al content is less than 0.001%. Therefore, the Al content is set to 0.001% or more. The Al content is preferably 0.003% or more or 0.010% or more.
[0082] On the other hand, even if the Al content is set to more than 0.300%, the above effect is saturated. In addition, due to the promotion of ferrite transformation, the desired metal structure cannot be obtained. Therefore, the Al content is set to 0.300% or less. The Al content is preferably 0.100% or less or 0.050% or less.
[0083] Ti: 0.001~0.100%
[0084] Ti improves the strength of hot rolled steel sheets by finely precipitating in the steel sheet as carbides. In addition, Ti fixes N by forming nitrides and inhibits the coarsening of austenite grains. When the Ti content is less than 0.001%, the above effects cannot be obtained. In addition, the metal structure at a position 200 μm from the surface cannot be preferably controlled. The desired bendability cannot be obtained. Therefore, the Ti content is set to 0.001% or more. The Ti content is preferably 0.005% or more or 0.010% or more.
[0085] On the other hand, if the Ti content exceeds 0.100%, a large amount of coarse carbides and nitrides will precipitate in the steel, and the workability of the hot-rolled steel sheet will decrease. Therefore, the Ti content is set to 0.100% or less. The Ti content is preferably 0.050% or less or 0.030% or less.
[0086] B: 0.0005~0.0050%
[0087] B segregates in the austenite grain boundaries, and even a small content significantly improves the hardenability, thereby improving the strength of the hot-rolled steel sheet. When the B content is less than 0.0005%, the above effect cannot be obtained. Therefore, the B content is set to 0.0005% or more. The B content is preferably 0.0010% or more or 0.0013% or more.
[0088] On the other hand, if the B content exceeds 0.0050%, the recrystallization of austenite during hot rolling is inhibited, the rolling load increases, and the desired metal structure cannot be obtained. Therefore, the B content is set to 0.0050% or less. The B content is preferably 0.0040% or less or 0.0030% or less.
[0089] The remainder of the chemical composition of the hot-rolled steel sheet of the present embodiment may also be Fe and impurities. In the present embodiment, the so-called impurities refer to components mixed from ore, waste materials or manufacturing environment as raw materials, or components allowed within a range that does not adversely affect the hot-rolled steel sheet of the present embodiment.
[0090] The hot-rolled steel sheet of the present embodiment may contain the following optional elements in place of a portion of Fe. When the optional elements are not contained, the lower limit of the content is 0%. Each optional element will be described below.
[0091] Nb: 0.005~0.100%
[0092] Nb precipitates in steel as carbides or nitrides to increase the strength of hot-rolled steel sheets. In addition, these precipitates inhibit the coarsening of austenite grains and promote the refinement of metal structures. In order to reliably obtain these effects, the Nb content is preferably set to 0.005% or more.
[0093] On the other hand, if the Nb content exceeds 0.100%, a large amount of coarse carbides and nitrides will precipitate in the steel, and the workability of the hot-rolled steel sheet will decrease. Therefore, the Nb content is set to 0.100% or less. Preferably, the Nb content is 0.030% or less.
[0094] Cr: 0.005~1.00%
[0095] Cr improves hardenability and increases the strength of the hot-rolled steel sheet. In order to reliably obtain this effect, the Cr content is preferably set to 0.005% or more.
[0096] On the other hand, if the Cr content exceeds 1.00%, the weldability of the hot-rolled steel sheet decreases. Therefore, the Cr content is set to 1.00% or less. The Cr content is preferably 0.30% or less.
[0097] V: 0.005~0.30%
[0098] V contributes to the strength of the hot rolled steel sheet by being dissolved in the steel and also contributes to the strength of the hot rolled steel sheet by precipitation strengthening as carbides, nitrides or carbonitrides in the steel sheet. In order to reliably obtain these effects, the V content is preferably set to 0.005% or more.
[0099] On the other hand, if the V content exceeds 0.30%, the toughness of the hot-rolled steel sheet decreases. Therefore, the V content is set to 0.30% or less. The V content is preferably 0.10% or less.
[0100] Cu: 0.005~0.30%
[0101] Cu dissolves in steel to contribute to increasing the strength of the hot-rolled steel sheet and also contributes to improving corrosion resistance. In order to reliably obtain these effects, the Cu content is preferably set to 0.005% or more.
[0102] On the other hand, if the Cu content exceeds 0.30%, the surface properties of the hot-rolled steel sheet deteriorate. Therefore, the Cu content is set to 0.30% or less. The Cu content is preferably 0.10% or less.
[0103] Ni: 0.005~0.30%
[0104] Ni dissolves in steel to contribute to the increase in strength of the hot-rolled steel sheet and also contribute to the improvement in toughness. In order to reliably obtain these effects, the Ni content is preferably set to 0.005% or more.
[0105] Ni is an expensive element. Even if the Ni content is set to more than 0.30%, the alloy cost will increase. Therefore, the Ni content is set to 0.30% or less. The Ni content is preferably 0.10% or less.
[0106] Ca: 0.0010~0.0050%
[0107] Ca refines oxides and nitrides precipitated during solidification to improve the cleanliness of the steel ingot or billet. In order to reliably obtain this effect, the Ca content is preferably set to 0.0010% or more.
[0108] On the other hand, even if more than 0.0050% of Ca is contained, the above-mentioned effect is saturated, resulting in an increase in cost. Therefore, the Ca content is set to 0.0050% or less. The Ca content is preferably 0.0030% or less.
[0109] The chemical composition of the hot-rolled steel sheet can be measured by general analytical methods. For example, ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry) and optical emission spectrometry (OES) can be used for measurement. In addition, C and S can be measured by the combustion-infrared absorption method, and N can be measured by the inert gas melting-thermal conductivity method.
[0110] Regarding the chemical composition of the hot-rolled steel sheet of the present embodiment, Vc represented by the following formulas (1) to (3) is 10 to 40. If Vc is less than 10 or exceeds 40, the metal structure cannot be properly controlled at the 1 / 4 thickness position and / or the position 200 μm from the surface.
[0111] It should be noted that the effective B amount in the following formula (1) is the B amount that contributes to hardenability and can be obtained by the following formula (2). In addition, the dissolved N amount in the following formula (2) can be obtained by the following formula (3).
[0112] When the effective B content is ≥ 0.0005 mass %,
[0113] Vc=10 2.94-0.75×(2.7×C+0.4×Si+Mn+0.45×Ni+0.8×Cr)
[0114] When the effective B content is less than 0.0005 mass%,
[0115] Vc=10 3.69-0.75×(2.7×C+0.4×Si+Mn+0.45×Ni+0.8×Cr) (1)
[0116] Effective B content = 10.81 × (B / 10.81-solid solution N content / 14.01) (2)
[0117] Solid solution N content = 14.01 × (N / 14.01-Ti / 47.88) (3)
[0118] The symbol of each element in the above formula (1) represents the content of the element in mass %, and 0 is substituted when the element is not contained.
[0119] B in the above formula (2) is the B content expressed in mass %. When the effective B amount is a negative value, the effective B amount is set to 0.
[0120] In the above formula (3), N and Ti are contents expressed in mass %. When the amount of dissolved N is a negative value, the amount of dissolved N is set to 0.
[0121] Next, the metal structure of the hot-rolled steel sheet according to the present embodiment will be described.
[0122] The metal structure of the hot-rolled steel sheet of this embodiment is calculated by area %:
[0123] At the 1 / 4 thickness position, at least one of martensite and tempered martensite accounts for 90% or more in total, and at least one of ferrite, bainite and pearlite accounts for 10% or less in total;
[0124] At a position 200 μm from the surface, at least one of martensite and tempered martensite accounts for 70% or more and less than 90% in total, and at least one of ferrite, bainite and pearlite accounts for more than 10% and less than 30% in total.
[0125] Each provision will be described in detail below.
[0126] Plate thickness 1 / 4 position
[0127] In this embodiment, the so-called 1 / 4 plate thickness position specifically refers to the area 10 μm from the front and back of the 1 / 4 plate thickness position, that is, the position of 1 / 4-10 μm from the surface to the position of 1 / 4+10 μm from the surface. In other words, it is an area with the position of 1 / 4-10 μm from the surface as the starting point and the position of 1 / 4+10 μm from the surface as the end point.
[0128] One or more of martensite and tempered martensite: 90% or more in total
[0129] Martensite and tempered martensite are hard, homogeneous and fine structures. By including these structures, high strength can be obtained. If the total area ratio of these structures is less than 90%, the desired strength cannot be obtained. Therefore, the total area ratio of these structures is set to be 90% or more. It should be noted that it is not necessary to include both martensite and tempered martensite. Even if only one of them is included, as long as the area ratio is 90% or more, it will be fine. The total area ratio of martensite and tempered martensite is preferably 92% or more or 95% or more. More preferably, it is 100%.
[0130] One or more of ferrite, bainite and pearlite: 10% or less in total
[0131] The hot-rolled steel sheet of this embodiment may also contain ferrite, bainite and pearlite as the remaining structure other than martensite and tempered martensite in the metal structure at the position of 1 / 4 of the plate thickness. If the total area ratio of these exceeds 10%, the strength of the hot-rolled steel sheet decreases. Therefore, the total area ratio of ferrite, bainite and pearlite is set to 10% or less. Preferably, it is 8% or less, 5% or less. More preferably, it is 0%.
[0132] It should be noted that it is not necessary to include all of ferrite, bainite, and pearlite.
[0133] 200μm from the surface
[0134] In this embodiment, the so-called 200 μm position from the surface specifically refers to the region 10 μm inside and outside the "200 μm position from the surface", that is, the 200 μm-10 μm (190 μm) position from the surface to the 200 μm+10 μm (210 μm) position from the surface. In other words, it is a region starting from the 190 μm position from the surface in the plate thickness direction and ending at the 210 μm position from the surface in the plate thickness direction.
[0135] One or more of martensite and tempered martensite: 70% or more and less than 90% in total
[0136] As mentioned above, martensite and tempered martensite are hard, homogeneous and fine structures. These structures are suitable for obtaining high-strength structures, but have poor bendability. In the hot-rolled steel sheet of this embodiment, in order to obtain the desired bendability, the area ratio of martensite and tempered martensite at a position 200 μm from the surface is reduced compared with the area ratio of martensite and tempered martensite at a position 1 / 4 of the plate thickness. If the total area ratio of martensite and tempered martensite at a position 200 μm from the surface is more than 90%, the bendability of the hot-rolled steel sheet deteriorates. Therefore, the total area ratio of these structures is set to less than 90%. Preferably, it is less than 87% or less than 85%.
[0137] If the total area ratio of martensite and tempered martensite is less than 70%, the desired strength cannot be obtained. Therefore, the total area ratio of these structures is set to 70% or more, preferably 75% or more.
[0138] Furthermore, the difference between the total of martensite and tempered martensite at a position of 1 / 4 of the plate thickness and the total area ratio of martensite and tempered martensite at a position 200 μm from the surface (= "the total of martensite and tempered martensite at a position of 1 / 4 of the plate thickness" - "the total area ratio of martensite and tempered martensite at a position 200 μm from the surface") is preferably 5% or more, more preferably 10% or more or 15% or more.
[0139] It should be noted that it is not necessary to contain both martensite and tempered martensite, and even when only one of them is contained, the area ratio thereof may be 70% or more and less than 90%.
[0140] One or more of ferrite, bainite and pearlite: more than 10% and less than 30%
[0141] The hot-rolled steel sheet of this embodiment may also contain ferrite, bainite and pearlite as residual structures other than martensite and tempered martensite in the metal structure at a position of 200 μm from the surface. These structures have poor strength, but excellent bendability. If the total area ratio of these structures is less than 10%, excellent bendability cannot be obtained. Therefore, the total area ratio of these structures is set to more than 10%. Preferably, it is more than 15%. It should be noted that it is not necessary to include all of ferrite, bainite and pearlite. Even if only any one of them is included, as long as its content exceeds 10%, it will be fine.
[0142] Furthermore, if the total area ratio of these structures exceeds 30%, the desired strength cannot be obtained. Therefore, the total area ratio of these structures is set to 30% or less, preferably 25% or less.
[0143] In the present embodiment, in addition to the metal structure at a position of 1 / 4 of the plate thickness and the metal structure at a position of 200 μm from the surface, the metal structure at a position of 100 μm from the surface can also be controlled.
[0144] The metal structure at a position 100 μm from the surface preferably comprises 60 to 80% in total of one or more of martensite and tempered martensite and 20 to 40% in total of one or more of ferrite, bainite and pearlite.
[0145] 100 μm from the surface
[0146] In this embodiment, the so-called 100 μm position from the surface specifically refers to the region where the "100 μm position from the surface" is 10 μm inside and outside, that is, the 100 μm-10 μm (90 μm) position from the surface to the 100 μm+10 μm (110 μm) position from the surface. In other words, it is a region starting from the 90 μm position from the surface in the plate thickness direction and ending at the 110 μm position from the surface in the plate thickness direction.
[0147] One or more of martensite and tempered martensite: 60-80% in total
[0148] By setting the total area ratio of martensite and tempered martensite to 80% or less, the bendability of the hot-rolled steel sheet can be improved. Therefore, the total area ratio of these structures is preferably set to 80% or less.
[0149] By setting the total area ratio of martensite and tempered martensite to 60% or more, the strength can be improved. Therefore, the total area ratio of these structures is preferably set to 60% or more.
[0150] It should be noted that it is not necessary to contain both martensite and tempered martensite, and even when only one of them is contained, the area ratio of either one of them may be 60 to 80%.
[0151] One or more of ferrite, bainite and pearlite: 20-40% in total
[0152] The hot-rolled steel sheet of this embodiment may also contain ferrite, bainite and pearlite as the remaining structures other than martensite and tempered martensite in the metal structure at a position of 100 μm from the surface. By setting the total area ratio of these structures to 20% or more, the bendability can be improved. Therefore, the total area ratio of these structures is preferably set to 20% or more. It should be noted that it is not necessary to include all of ferrite, bainite and pearlite. Even if only any one of them is included, as long as its content is 20% or more, it will be fine.
[0153] Furthermore, by setting the total area ratio of these structures to 40% or less, the strength can be improved. Therefore, the total area ratio of these structures is preferably set to 40% or less.
[0154] Hereinafter, the method for measuring the area ratio of each structure will be described.
[0155] Test pieces were collected from the hot-rolled steel sheets so that the metal structures at 100 μm, 200 μm and 1 / 4 of the thickness from the surface could be observed in a thickness cross section parallel to the rolling direction.
[0156] The cross section of the test piece is polished with #600 to #1500 silicon carbide paper, and then finished into a mirror surface using a liquid obtained by dispersing diamond powder with a particle size of 1 to 6 μm in a diluent such as alcohol or pure water. Next, the strain introduced into the surface layer of the sample is removed by polishing with colloidal silica that does not contain an alkaline solution at room temperature. At any position in the length direction of the sample cross section, the crystal orientation information is obtained by measuring 150 μm in the rolling direction × 20 μm in the plate thickness direction at a measurement interval of 0.1 μm by electron backscatter diffraction.
[0157] For the measurement, an EBSD analysis device consisting of a thermal field emission scanning electron microscope (JSM-7001F manufactured by JEOL) and an EBSD detector (DVC5 detector manufactured by TSL) was used. At this time, the vacuum degree in the EBSD analysis device was set to 9.6×10 -5Pa or less, the acceleration voltage was set to 15 kV, the irradiation current level was set to 13, and the electron beam irradiation level was set to 62. The obtained crystal orientation information was used using the "Phase Map" function installed in the software "OIM Analysis (registered trademark)" attached to the EBSD analysis device, and the crystal structure of bcc was judged as bainite, ferrite and "pearlite, martensite and tempered martensite".
[0158] For these regions, the "Grain Orientation Spread" function installed in the software "OIM Analysis (registered trademark)" attached to the EBSD analysis device was used to extract the region with a "Grain Orientation Spread" of 1° or less as ferrite under the condition that the 15° grain boundary was defined as the crystal grain boundary. The area ratio of the extracted ferrite was calculated to obtain the area ratio of ferrite.
[0159] Next, under the condition that the 5° grain boundary in the remaining region (region where "Grain Orientation Spread" exceeds 1°) is defined as a crystal grain boundary, when the maximum value of "Grain Average IQ" in the ferrite region is taken as Iα, the region exceeding Iα / 2 is extracted as bainite, and the region below Iα / 2 is extracted as "pearlite, martensite, and tempered martensite." The area ratio of the extracted bainite is calculated to obtain the area ratio of bainite.
[0160] Regarding the above-extracted “pearlite, martensite, and tempered martensite”, pearlite, martensite, and tempered martensite can be distinguished by the following method.
[0161] First, in order to observe the same area as the EBSD measurement area with SEM, a Vickers indentation was made near the observation position. After that, the surface dirt was polished off while leaving the structure of the observation surface, and nital etching was performed. Next, the same field of view as the EBSD observation surface was observed with SEM at a magnification of 3000 times.
[0162] Among the regions identified as “pearlite, martensite, and tempered martensite” in the EBSD measurement, a region having a lower structure in a grain and in which cementite is precipitated in a plurality of variants is identified as tempered martensite.
[0163] The region where cementite precipitates in lamellar form is judged to be pearlite.
[0164] A region with high brightness and no underlying structure due to etching was judged to be martensite.
[0165] By calculating the respective area ratios, the area ratios of tempered martensite, pearlite, and martensite are obtained.
[0166] In addition, the surface layer of the observation surface can be cleaned by polishing using aluminum oxide particles with a particle size of 0.1 μm or less, or by Ar ion sputtering or the like.
[0167] The above-mentioned measurement was performed at a position 100 μm from the surface, a position 200 μm from the surface, and a position 1 / 4 of the plate thickness from the surface to obtain the area ratio of the metal structure at each position.
[0168] In the hot-rolled steel sheet of the present embodiment, in the metal structure at a position of 1 / 4 of the sheet thickness, the average aspect ratio of prior austenite grains is preferably 1.0 to 3.0.
[0169] Furthermore, in the metal structure at a position of 1 / 4 of the plate thickness, the average grain size of prior austenite grains is preferably 5 to 40 μm.
[0170] Average aspect ratio of original austenite grains: 1.0~3.0
[0171] In the metal structure at the 1 / 4 thickness position, by setting the average aspect ratio of prior austenite grains to 1.0 to 3.0, anisotropy in properties can be reduced, and as a result, the bendability of the hot-rolled steel sheet can be further improved.
[0172] It should be noted that the aspect ratio of the original austenite grain refers to the value obtained by dividing the major axis of the original austenite grain by the minor axis, and takes a value of 1.0 or more. The smaller the aspect ratio, the more equiaxed the grain is, and the larger the aspect ratio, the flatter the grain becomes. The aspect ratio becomes an index representing the degree of anisotropy of the characteristics.
[0173] The average grain size of the original austenite grains: 5 to 40 μm
[0174] In the metal structure at a position of 1 / 4 of the plate thickness, by setting the average grain size of prior austenite grains to 5 to 40 μm, the bendability can be further improved.
[0175] Hereinafter, a method for measuring the average aspect ratio and average grain size of prior austenite grains at a position of 1 / 4 of the plate thickness will be described.
[0176] From the hot-rolled steel plate, a test piece is collected in such a way that the metal structure at a position 1 / 4 of the plate thickness can be observed from the surface in the plate thickness section parallel to the rolling direction. The original austenite grain boundary is revealed by corroding the observation surface with a saturated aqueous solution of picric acid. The enlarged photograph of the cross section parallel to the rolling direction after corrosion treatment at a position 1 / 4 of the plate thickness from the surface is photographed using a scanning electron microscope (SEM) at a magnification of 1000 times for more than 5 fields of view of 100μm×100μm. The equivalent circle diameter (diameter) of at least 20 original austenite grains with an equivalent circle diameter (diameter) of 2μm or more contained in each SEM photograph is obtained by image processing. By calculating these average values, the average grain size of the original austenite grains is obtained. In the case of original austenite grains with an equivalent circle diameter of less than 2μm, they are excluded to implement the above-mentioned measurement.
[0177] In addition, the major axis and minor axis of at least 20 original austenite grains with an equivalent circle diameter (diameter) of 2 μm or more contained in each of the above-mentioned SEM photographs are measured. The average major axis and the average minor axis of the original austenite grains are obtained by calculating the average value of the major axis and the minor axis obtained by measuring each original austenite grain. By calculating their ratio (average major axis / average minor axis), the average aspect ratio of the original austenite grains is obtained.
[0178] Tensile strength: above 980MPa
[0179] The tensile (maximum) strength of the hot-rolled steel sheet of this embodiment may also be 980 MPa or more. By setting the tensile strength to 980 MPa or more, the application parts are not limited, and the contribution to the lightweighting of the vehicle body can be increased. More preferably, the tensile strength is 1000 MPa or more, 1100 MPa or more.
[0180] The upper limit of the tensile strength does not need to be particularly limited, but may be set to 1470 MPa from the viewpoint of suppressing die wear.
[0181] The tensile strength was measured using a No. 5 test piece of JIS Z 2241: 2011 in accordance with JIS Z 2241: 2011. The tensile test piece was collected at the center of the sheet width direction, and the direction perpendicular to the rolling direction was set as the longitudinal direction.
[0182] R / t: 1.5 or less
[0183] The hot rolled steel sheet of this embodiment may have a ratio R / t of the limit bending radius R to the sheet thickness t obtained by a test according to the V-block method described below, which may be 1.5 or less. If R / t is 1.5 or less, it can be determined that the hot rolled steel sheet has excellent bendability.
[0184] R / t is obtained by the following method.
[0185] A 100 mm x 30 mm strip test piece was cut from the half position in the width direction of the hot rolled steel sheet. For bending (L axis bending) with the bending ridgeline parallel to the rolling direction (L direction), the test was conducted according to the V-block method of JIS Z 2248:2006 (bending angle θ is 90°). The minimum bending radius R without cracking was obtained and divided by the plate thickness t to obtain the limit bending R / t.
[0186] However, regarding the presence or absence of cracks, the bent surface of the test piece after the V-block 90° bending test was observed for cracks using a magnifying glass or an optical microscope at a magnification of 10 times or more, and cracks were judged to be present when the length of the cracks observed on the bent surface of the test piece exceeded 0.5 mm.
[0187] Plate thickness: more than 0.8mm and less than 8.0mm
[0188] The plate thickness of the hot-rolled steel sheet of the present embodiment is not particularly limited, but may also be set to be greater than 0.8 mm and less than 8.0 mm. When the plate thickness of the hot-rolled steel sheet is less than 0.8 mm, it is sometimes difficult to ensure the rolling completion temperature, and the rolling load becomes too large, making hot rolling difficult. Therefore, the plate thickness of the hot-rolled steel sheet of the present embodiment may also be set to be greater than 0.8 mm. Preferably, it is greater than 1.2 mm or greater than 1.4 mm.
[0189] On the other hand, when the plate thickness exceeds 8.0 mm, it may become difficult to obtain the above-mentioned metal structure. Therefore, the plate thickness may be set to 8.0 mm or less, preferably 6.0 mm or less.
[0190] Plating
[0191] The hot rolled steel sheet of the present embodiment with the above-mentioned chemical composition and metal structure can also make the surface equipped with a coating to make a surface treated steel sheet for the purpose of improving corrosion resistance. The coating can be an electroplated layer or a hot dip coating. As the electroplated layer, an electrogalvanized layer, an electroplated Zn-Ni alloy layer, etc. can be exemplified. As the hot dip coating, a hot dip galvanized layer, an alloyed hot dip galvanized layer, a hot dip aluminum layer, a hot dip Zn-Al alloy layer, a hot dip Zn-Al-Mg alloy layer, a hot dip Zn-Al-Mg-Si alloy layer, etc. can be exemplified. The coating adhesion amount is not particularly limited, and it can be set to be the same as before. In addition, it is also possible to implement appropriate chemical conversion treatment (for example, the coating and drying of the chromium-free chemical conversion treatment liquid of the silicate system) after plating to further improve corrosion resistance.
[0192] Next, a preferred method for producing the hot-rolled steel sheet according to the present embodiment will be described. It should be noted that the temperature of the slab and the temperature of the steel sheet in the present embodiment refer to the surface temperature of the slab and the surface temperature of the steel sheet.
[0193] A preferred method for producing a hot-rolled steel sheet according to the present embodiment includes the following steps.
[0194] The slab having the above-mentioned chemical composition is heated to a temperature range of 1100 to 1250°C.
[0195] The rough rolling is performed so that the rough rolling completion temperature becomes 1000 to 1100°C.
[0196] Finish rolling was performed so as to satisfy the following conditions.
[0197] (I) The steel plate tension between the final pass and the pass immediately before the final pass is 2.0 to 5.0 kg / mm 2 .
[0198] (II) The finishing rolling completion temperature FT is Ac3 point + 10°C to Ac3 point + 30°C.
[0199] (III) The reduction rate of the final pass is 20 to 40%.
[0200] Cooling is performed so that the average cooling rate in the temperature range from the finish rolling completion temperature FT to the Ms point becomes Vc+10°C / sec to Vc+40°C / sec.
[0201] The cooling is stopped in the temperature range of Ms point - 200°C or lower, and then the steel is coiled.
[0202] However, in the finish rolling, it is more preferable to satisfy the condition (IV) that the cumulative reduction ratio is 75 to 95%.
[0203] Hereinafter, each step will be described in detail.
[0204] Slab heating temperature: 1100~1250℃
[0205] The slab having the above chemical composition is preferably heated to a temperature range of 1100 to 1250° C. If the heating temperature of the slab is lower than 1100° C., deformation resistance during hot rolling may be high and rolling load may increase. Therefore, the heating temperature is preferably set to 1100° C. or higher.
[0206] On the other hand, if the heating temperature exceeds 1250° C., prior austenite grains may coarsen, and the low-temperature toughness of the hot-rolled steel sheet may decrease. Therefore, the heating temperature is preferably set to 1250° C. or less.
[0207] Furthermore, from the viewpoint of manufacturing cost, the heated slab is preferably produced by continuous casting, but may also be produced by other casting methods (eg, ingot casting).
[0208] Rough rolling completion temperature: 1000~1100℃
[0209] Hot rolling is generally divided into rough rolling and finish rolling. In order to make the slab into a rough bar of desired size and shape and to easily adjust the finish rolling finish temperature to a desired range, rough rolling is preferably performed so that the rough rolling finish temperature is 1000 to 1100°C.
[0210] Finish rolling
[0211] (I) Steel sheet tension between the final pass and the pass immediately before the final pass: 2.0 to 5.0 kg / mm 2
[0212] In the finish rolling, the steel sheet tension between the final pass and the pass immediately before the final pass is set to 2.0 kg / mm. 2 As a result, friction can be preferentially generated between the roller and the surface area of the steel plate, and load-bearing shear strain can be introduced into the surface area. As a result, the desired metal structure can be obtained at a position 200 μm from the surface. If the steel plate tension exceeds 5.0 kg / mm 2 , the steel plate may break and finish rolling cannot be carried out stably.
[0213] The tension of the steel sheet can be adjusted by increasing the rotation speed of the final pass and / or the pass immediately before the final pass, or by increasing the loop.
[0214] (II) Finish rolling completion temperature FT: Ac3 point + 10°C ~ Ac3 point + 30°C
[0215] By setting the finishing temperature FT to Ac3 point + 10°C or more, it is possible to suppress the formation of a large amount of ferrite and bainite at a position 200 μm from the surface, and as a result, it is possible to obtain a desired amount of martensite and tempered martensite. In addition, by setting the finishing temperature FT to Ac3 point + 30°C or less, it is possible to suppress the release of the strain in the surface area imparted in the final pass of the finishing rolling. As a result, it is possible to suppress the amount of martensite at a position 200 μm from becoming excessive.
[0216] In this embodiment, the Ac3 point is represented by the following formula.
[0217] Ac3=937.2-436.5×C+56×Si-19.7×Mn-16.3×Cu-26.6×Ni-4.9×Cr+124.8×V+136.3×Ti-19.1×Nb+198.4×Al+3315×B
[0218] Each element symbol in the above formula represents the content of the element in mass %, and 0 is substituted when the element is not contained.
[0219] (III) Final pass reduction rate: 20-40%
[0220] In order to set the martensite at a position of 200 μm from the surface to the desired amount, it is preferred to set the reduction rate of the final pass to 20-40%. By setting the reduction rate to 20% or more, the amount of strain introduced into the surface area will not be insufficient, and the driving force for the transformation of ferrite, bainite and pearlite can be fully ensured. In addition, by setting the reduction rate to 40% or less, the driving force for the transformation of ferrite, bainite and pearlite can be suppressed from becoming excessive. As a result, the metal structure at a position of 200 μm from the surface can be preferably controlled.
[0221] The reduction ratio in the final pass of the finish rolling is obtained by dividing the plate thickness t0 of the steel plate before the final pass by the plate thickness t1 of the steel plate after the final pass ((1-t0 / t1)×100).
[0222] (IV) Cumulative reduction rate: 75-95%
[0223] This condition is a more preferred condition. The cumulative reduction rate in the finish rolling is calculated by changing the thickness t of the steel plate before the finish rolling to i Divide by the thickness of the steel plate after finishing rolling t f ((1-t i / t f By setting the cumulative reduction rate of finish rolling to 75 to 95%, the average grain size and average aspect ratio of prior austenite grains can be preferably controlled.
[0224] Average cooling rate in the temperature range from finishing temperature FT to Ms point: Vc+10℃ / sec to Vc+40℃ / sec
[0225] After the finish rolling is completed, the desired metal structure can be obtained by cooling to the temperature range where the austenite phase changes to martensite by water cooling. If the average cooling rate is too slow, ferrite and / or bainite may be generated during the cooling process, and the strength of the hot-rolled steel sheet will be reduced. Therefore, the average cooling rate in the temperature range from the finish rolling completion temperature FT to the Ms point is preferably set to Vc+10°C / second or more. In addition, if the average cooling rate is too fast, it may result in the failure to obtain the desired amount of martensite in the surface area. As a result, it may result in the failure to obtain excellent bendability. As a result, it may not be possible to preferably control the metal structure at a distance of 200μm from the surface. Therefore, the average cooling rate in the temperature range from the finish rolling completion temperature FT to the Ms point is set to Vc+40°C / second or less.
[0226] It is preferable that water cooling at the above average cooling rate be performed to a cooling stop temperature described later.
[0227] The average cooling rate here is set to a value obtained by dividing the temperature difference between the start point and the end point of the set range by the elapsed time from the start point to the end point.
[0228] It should be noted that Vc is represented by the above formulae (1) to (3).
[0229] The Ms point is expressed by the following formula.
[0230] Ms=561-474×C-33×Mn-17×Ni
[0231] Each element symbol in the above formula represents the content of the element in mass %, and 0 is substituted when the element is not contained.
[0232] Cooling stop temperature (coiling temperature): Ms point -200℃ or below
[0233] The cooling stop temperature is preferably set to Ms point - 200° C. or lower. It is more preferably Ms point - 250° C. or lower, and further preferably Ms point - 300° C. or lower. After cooling is stopped, coiling is performed.
[0234] The lower limit of the cooling stop temperature is not particularly limited, and may be set to room temperature (25° C.).
[0235] The hot-rolled steel sheet of the present embodiment can be manufactured by the method described above. If necessary, the above-mentioned plating layer may be formed on the surface of the hot-rolled steel sheet.
[0236] Example
[0237] Slabs having the chemical compositions shown in Tables 1A and 1B were produced by continuous casting. The obtained slabs were used to produce hot-rolled steel sheets shown in Tables 3A and 3B under the conditions shown in Tables 2A and 2B. Coiling was performed immediately after cooling to the cooling stop temperature shown in Tables 2A and 2B.
[0238] The obtained hot-rolled steel sheet was tested for metal structure, tensile strength and R / t at the position of 1 / 4 thickness, 200 μm from the surface and 100 μm from the surface by the above method. In addition, the total elongation (%) was obtained by the tensile test performed by the above method.
[0239] The obtained results are shown in Table 3A and Table 3B. It should be noted that the steel sheet tension represents the steel sheet tension between the final pass and the pass before the final pass. In addition, M represents martensite, TM represents tempered martensite, F represents ferrite, B represents bainite, and P represents pearlite. For some examples, since a large amount of ferrite, bainite and pearlite were generated, the morphology of the original austenite grains became unclear, and therefore the average aspect ratio and average grain size of the original austenite grains at the 1 / 4 position of the plate thickness could not be measured.
[0240] When the tensile strength is 980 MPa or more, it is determined to be acceptable as having high strength. On the other hand, when the tensile strength is less than 980 MPa, it is determined to be unacceptable as having poor strength.
[0241] When R / t is 1.5 or less, the bendability is excellent and is judged as acceptable. On the other hand, when R / t exceeds 1.5, the bendability is poor and is judged as unacceptable.
[0242] When the total elongation was 8.5% or more, the sample was judged to be acceptable as having excellent ductility.
[0243] [Table 1A]
[0244]
[0245] [Table 1B]
[0246]
[0247] [Table 2A]
[0248]
[0249] [Table 2B]
[0250]
[0251] [Table 3A]
[0252]
[0253] [Table 3B]
[0254]
[0255] As can be seen from Table 3A and Table 3B, the hot-rolled steel sheets of the examples of the present invention have high strength and excellent bendability.
[0256] On the other hand, it is found that the hot-rolled steel sheets of the comparative examples are inferior in one or more of the above-mentioned characteristics.
[0257] Industrial Applicability
[0258] According to the above aspects of the present invention, a hot-rolled steel sheet having high strength and excellent bendability can be provided.
Claims
1. A hot rolled steel plate, characterized in that: The chemical composition contains by mass %: C:0.050~0.150%、 Si: 0.01-1.00%, Mn: 1.00~2.50%, P: 0.100% or less, S: 0.020% or less, N: 0.0050% or less, Al:0.001~0.300%、 Ti: 0.001~0.100%, B:0.0005~0.0050%、 Nb: 0~0.100%, Cr:0~1.00%、 V:0~0.30%、 Cu: 0-0.30%, Ni: 0-0.30%, and Ca: 0~0.0050%, The rest contains Fe and impurities. Vc represented by the following formulas (1) to (3) is 10 to 40, Metallic structure in area %: At the 1 / 4 thickness position, at least one of martensite and tempered martensite accounts for more than 90% in total, and at least one of ferrite, bainite and pearlite accounts for less than 10% in total, and the average aspect ratio of the original austenite grains is 1.0 to 3.0; At a distance of 200 μm from the surface, at least one of martensite and tempered martensite accounts for 70% or more and less than 90% in total, and at least one of ferrite, bainite and pearlite accounts for more than 10% and less than 30% in total, When the effective B content is ≥ 0.0005 mass %, Vc=10 2.94-0.75×(2.7×C+0.4×Si+Mn+0.45×Ni+0.8×Cr) When the effective B content is less than 0.0005 mass%, Vc=10 3.69-0.75×(2.7×C+0.4×Si+Mn+0.45×Ni+0.8×Cr) (1) Effective B content = 10.81 × (B / 10.81-solid solution N content / 14.01) (2) Solid solution N content = 14.01 × (N / 14.01-Ti / 47.88) (3) The symbol of each element in the formula (1) is the content of the element in mass %, and 0 is substituted when the element is not contained. In the formula (2), B is the B content in mass %. When the effective B content is a negative value, the effective B content is set to 0. In the above formula (3), N and Ti are contents expressed in mass %, respectively. When the amount of dissolved N is a negative value, the amount of dissolved N is set to 0.
2. The hot rolled steel sheet according to claim 1, characterized in that: The chemical composition contains one or more of the following elements in mass %: Nb: 0.005~0.100% Cr:0.005~1.00%、 V:0.005~0.30%、 Cu: 0.005-0.30%, Ni: 0.005-0.30%, and Ca: 0.0010~0.0050%.
3. The hot rolled steel sheet according to claim 1 or 2, characterized in that: In the metal structure, at a position of 1 / 4 of the plate thickness, the average grain size of the original austenite grains is 5 to 40 μm.
Citation Information
Patent Citations
High strength hot rolled steel sheet and production method therefor
JP2016211073A
High strength hot-rolled steel sheet and production method thereof
JP2018188675A
Image forming apparatus
JP2021005008A
High-strength hot-rolled steel sheet having excellent bendability and low-temperature toughness and method for manufacturing same
CN111356781A